(untitled) (Applied Biological Research, 2023)
Fruit loss due to birds is a long-standing and costly problem affecting producers across the globe. The rose-ringed parakeet enjoys the status of worst avian pest in the Indian subcontinent. This study provides the information about the effectiveness of reflective ribbons in controlling the damage of rose-ringed parakeet (Psittacula krameri) to guava (Psidium guajava L.) fruit trees in central plain and sub-mountainous regions of Punjab (India). Thdamage causedby parakeet to the control fields ranged from 12.13 to 16.76% while the fields installed with reflective ribbons had damage between 5.67 and 8.51%. Ripened fruits were more preferred with top canopy most affected part of the trees. A remarkable reduction in bird damage was noticed in presence of reflective ribbons. Therefore, it seems plausible to use reflective ribbons as bird repellents to reduce bird depredatory attacks, improve economic losses and augment the crop quality and production.